1980
DOI: 10.1002/pen.760201710
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the influence of molecular weight distribution on the rheological properties of polypropylene melts

Abstract: An experimental study of steady shear and elongational flow Theological properties of a series of polypropylene melts of varying molecular weight and distribution is reported. Broadening the molecular weight distribution increases the non‐Newtonian character of the shear viscosity function and increases the principal normal stress differences at fixed shear stress. The behavior is compared to earlier rheological property‐molecular weight studies. Correlations are developed for these properties in terms of mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 136 publications
(58 citation statements)
references
References 63 publications
6
52
0
Order By: Relevance
“…We have carried out such measurements in an earlier study. 28 In Figure 6 we compare the results of elongational viscosities determined from local point by point spinline measurements and from simple elongational flow. For the PP-H-N and the PP-M-N, the x values from the simple elongational flow experiments are equal to 3710 at low elongation rates and increase at higher rates of deformation.…”
Section: Discussion Of Resultsmentioning
confidence: 98%
“…We have carried out such measurements in an earlier study. 28 In Figure 6 we compare the results of elongational viscosities determined from local point by point spinline measurements and from simple elongational flow. For the PP-H-N and the PP-M-N, the x values from the simple elongational flow experiments are equal to 3710 at low elongation rates and increase at higher rates of deformation.…”
Section: Discussion Of Resultsmentioning
confidence: 98%
“…Fox and Flory theory has been confirmed by numerous investigations (Fox and Loshaek (1955), Fox et al (1956), Baumann andSteingiser (1963), Gruver et al (1964), Kraus and Gruver (1965), Minoshima et al (1980)). Generally, it was found that for polydisperse systems that molecular weight which should be used is the weight average MW (M w ).…”
Section: Gel Permeation Chromatography Analysismentioning
confidence: 50%
“…The observed polydispersity index ranges from 3 to 5. This is comparable to branched PP [12,51] or blends of different types of PS [15,52]. Table 4.…”
Section: Influence Of Plasticizer On Melt Strength and Melt Extensibimentioning
confidence: 72%